2010
DOI: 10.1111/j.1365-2222.2010.03524.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G‐dependent changes in basophil allergen threshold sensitivity during birch pollen immunotherapy

Abstract: In this study, we showed that birch immunotherapy-induced IgG antibodies are associated with a reduction in basophil allergen threshold sensitivity. Further studies are needed to show whether the changes in basophil sensitivity are of clinical relevance in pollen immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 32 publications
(68 reference statements)
5
76
0
Order By: Relevance
“…Similarly, Lalek et al [33] demonstrated that perennial SCIT with a birch pollen allergoid led to reduced CD63 expression, which correlated with patient symptoms assessed by a visual analog scale. They also firstly revealed the reduced inhibitory effect of the patient’s serum after elimination of the IgG antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Lalek et al [33] demonstrated that perennial SCIT with a birch pollen allergoid led to reduced CD63 expression, which correlated with patient symptoms assessed by a visual analog scale. They also firstly revealed the reduced inhibitory effect of the patient’s serum after elimination of the IgG antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This study stresses the prominent role of IgG antibodies in decreased basophil activation to allergen challenge in the basophil activation test. The blocking IgG antibodies most likely bind to allergen and thus reduce free allergen concentrations in the vicinity of mast cells and basophils [33]. Cady et al [34] demonstrated that IgG antibodies produced during subcutaneous immunotherapy with a cat extract also inhibited basophil responses to allergen via binding to both FcγRIIA and inhibitor FcγRIIB immunoglobulin Fc receptors expressed by basophils.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of basophil activation after discontinuation of AIT has been demonstrated 12-24 months following discontinuation of treatment [Nopp et al 2009;Lalek et al 2010;Gokmen et al 2012;Shamji et al 2015;Zidarn et al 2015].…”
Section: Cellular Changesmentioning
confidence: 99%
“…In the third study [4], blood samples were taken at a median delay of 833 days after the onset of sCAD symptoms. Lindgren et al [18] reported an increase in the median tHcy level from 11.4 to 14.5 µmol/l from the acute (mean 2 days after stroke onset) to the chronic phase (median 583 days after stroke onset). Thus, the later blood sampling might explain the higher tHcy values and prevalence of mild hyperhomocysteinemia reported in previous studies [3,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elevated tHcy could be the consequence of cerebral ischemia or also an infection which has been shown to be associated with sCAD [21, 22] rather than a cause of the disease. Also, food deprivation increases the tHcy levels [18, 23, 24]. In acute stroke, patients are kept fasting, and tHcy may therefore increase independently of the ischemic process.…”
Section: Discussionmentioning
confidence: 99%